1999
DOI: 10.1083/jcb.144.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of FAK/p130CAS/c-Src Complex during Mitosis: Role of Mitosis-specific Serine Phosphorylation of FAK

Abstract: At mitosis, focal adhesions disassemble and the signal transduction from focal adhesions is inactivated. We have found that components of focal adhesions including focal adhesion kinase (FAK), paxillin, and p130CAS (CAS) are serine/threonine phosphorylated during mitosis when all three proteins are tyrosine dephosphorylated. Mitosis-specific phosphorylation continues past cytokinesis and is reversed during post-mitotic cell spreading.We have found two significant alterations in FAK-mediated signal transduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 75 publications
(96 reference statements)
7
107
0
Order By: Relevance
“…Several reports pointed out a tyrosine dephosphorylation of the components of the focal adhesion complex including FAK, paxillin and p130 Cas associated with ser/thr phosphorylation of these proteins and the dissociation of the complex during the M phase of the cell cycle. This suggests that focal adhesion protein interaction is linked to ser/thr phosphorylation status [23,24]. Aurora-A is a member of Aurora kinase family that includes three members, Aurora-A, -B and -C. All of them are regulators of mitosis and Aurora-A and -B are overexpressed in a variety of tumor cell lines suggesting a role in tumorigenesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports pointed out a tyrosine dephosphorylation of the components of the focal adhesion complex including FAK, paxillin and p130 Cas associated with ser/thr phosphorylation of these proteins and the dissociation of the complex during the M phase of the cell cycle. This suggests that focal adhesion protein interaction is linked to ser/thr phosphorylation status [23,24]. Aurora-A is a member of Aurora kinase family that includes three members, Aurora-A, -B and -C. All of them are regulators of mitosis and Aurora-A and -B are overexpressed in a variety of tumor cell lines suggesting a role in tumorigenesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has become clear that FAK is also phosphorylated at multiple serine residues [32][33][34][35][36][37]. The proximity of these phosphorylated serine residues to sites at which FAK interacts with other proteins suggests a possible function in the regulation of the assembly of FAK signaling complexes [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, because adhesion is most readily observable in interphase cells, and focal adhesions tend to minimize or disappear in mitotic cells, accompanied by the down-regulation of some key focal adhesion-associated signaling proteins (Yamaguchi et al, 1997;Law et al, 1998;Yamakita et al, 1999), little work has investigated a possible requirement or alternative roles for adhesion-associated proteins in M phase. Similarly, it is only in the past several years that investigations of the nuclear cell cycle have documented the coordination of signaling events in time and space during M-phase progression, emphasizing the roles of proteins associated with structures such as the centrosome, the contractile ring, the central spindle, and the midbody (Raff et al, This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E05-03-0237) on January 4, 2006. 2002; reviewed in Glotzer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a number of proteins most studied in the context of action at focal adhesions, including zyxin (Hirota et al, 2000), paxillin (Yamaguchi et al, 1997), FAK (Yamakita et al, 1999;Fresu et al, 2001;Ma et al, 2001), and the Cas family member HEF1 (Law et al, 1998), have been implicated in mitotic control, based on dramatic changes in their phosphorylation, or their localization to mitotic structures, in M phase. We have begun to investigate the role of HEF1 as a direct regulator of mitotic progression, and through this work, we have recently demonstrated that HEF1 associates with and positively regulates the Aurora-A kinase at mitotic entry (Pugacheva and Golemis, 2005).…”
Section: Introductionmentioning
confidence: 99%